Sosialisasi Pengolahan Limbah Cair Teripang Menjadi Mikroorganisme Lokal (MOL) Kepada Kelompok Darmawisata Di Desa Benan Kabupaten Lingga Kepulauan Riau - Sari, T. Ersti Yulika; Putri, R.Marwita Sari; Amrizal, Sri Novalina; Muzammil, Wahyu; Oktavia, Yulia; Tetty, Tetty; Khairunnisa, Khairunnisa; Putri, Dwi Septiani; Ilhamdy, Aidil Fadli; Apriandi, Azwin; Zahra, Aminatul; Jumsurizal, Jumsurizal (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Benan is one of the islands located in Senayang District, Lingga Regency, Riau Islands. Most of the people on Benan Island work as sea cucumber fishermen, this is because the existence of sea cucumbers on the island is still abundant. The processing of liquid waste originating from post-harvest sea cucumbers in the form of wet sea cucumbers and dry sea cucumbers has not been carried out optimally, even though the more raw materials for sea cucumbers are prepared at the time of postharvest, the more waste generated will also be. The problem with partners is that the liquid waste originating from the post-harvest preparation of sea cucumbers has not been carried out optimally. The solution given to partners is education through socialization of liquid waste processing from the results of postharvest preparation of sea cucumbers into local microorganisms (MOL) in the Benan village field trip group, so that postharvest processing of sea cucumbers becomes zero waste. The methods in the activities carried out are discussion and socialization. The results obtained after this service is increasing public knowledge about sea cucumber wastewater treatment.